Theory of Relative Universality in Islam - Mohammad Reza Dehshiri (CV. FOUNDAE, 2025)
This article seeks to explain which position Islam has adopted amongst homogenous universal and non-homogenous relativist approaches and how it has managed to strike a balance between universalism and particularism. The author develops the hypothesis of “relative universality”, i.e. universality in the principles and relativity in the procedures and approaches, to explain that Islam has managed to establish a kind of dialectic between centripetal and centrifugal forces in the age of glocalization and to bring about harmony between universalism and particularism with a focus on alternative modernity. This article, based on the theoretical eclectic method, lays emphasis on the interaction between the context, structure, agent and processes at three levels of ontology, epistemology and methodology for the purpose of dialectic synthesis of contradictory concepts. The author concludes that the relative universality theory relies on overlapping values, extended rationality and organic linkage between content and form at the contextual level, on two-level legitimacy, pluralistic unity and multi-layered governance at the structural level, on interaction between sub-national, national and international actors at the agent level, and on general-particular intertwinement, tradition-modernity linkage and continuity despite change at the level of processes.